2015
DOI: 10.1097/crd.0000000000000047
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction and Coronary Artery Disease

Abstract: Atherosclerotic coronary artery disease (CAD) is a major cause of morbidity and mortality in the developed world. Endothelial dysfunction plays an important role in the development of atherosclerosis and predicts cardiovascular (CV) outcomes independent of conventional CV risk factors. In recent years, there have been tremendous improvements in the pharmacological prevention and management of CAD. In this review, the pathophysiology of endothelial dysfunction in relation to CAD is discussed and various techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 143 publications
0
25
0
1
Order By: Relevance
“…We found that CPB elicit endothelial toxicity which, in turn, defines their pathogenic effects since it is a crucial point in the development of atherosclerosis 59 60 . CPB promoted caspase-dependent apoptosis in endothelial cells, stimulated production of IL-6 and IL-8, which are established pro-atherosclerotic cytokines 61 62 , and induced intimal hyperplasia in vivo .…”
Section: Discussionmentioning
confidence: 89%
“…We found that CPB elicit endothelial toxicity which, in turn, defines their pathogenic effects since it is a crucial point in the development of atherosclerosis 59 60 . CPB promoted caspase-dependent apoptosis in endothelial cells, stimulated production of IL-6 and IL-8, which are established pro-atherosclerotic cytokines 61 62 , and induced intimal hyperplasia in vivo .…”
Section: Discussionmentioning
confidence: 89%
“…In the above mechanisms, the improvement of vascular endothelial function is reasonably important. Endothelial dysfunction plays an important role in the development of atherosclerosis and predicts CV outcomes independent of conventional CV risk factors [ 18 ]. Although the mechanism by which postprandial hyperglycemia induces endothelial dysfunction is not fully understood, oxidative stress-mediated disruptions in nitric oxide homeostasis are implicated as key role [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Normal endothelial function is promoted by exercise and a healthy diet, in addition to avoiding exposures known to be detrimental to endothelial function [87,88]. Abnormal endothelial cell function termed "endothelial dysfunction" is associated with vasoconstriction, poor vascular reactivity, pro-thrombosis, pro-adhesion, pro-inflammation, and growth promotion [89]. In addition, chronic endothelial dysfunction is associated with coronary artery disease, cerebrovascular disease, and peripheral arterial disease [89].…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%